Web animation using JavaScript - Shapiro, Julian, ....-; DeSandro, David, ....- (Berkeley : Peachpit Press, 2015)
Offers information on how to add animation in websites and apps that enriches a page with motion design while avoiding unnecessary flourishes, including leveraging JavaScript animation libraries like Velocity.js to streamline animation programming.
"Foreword by David DeSandro ..."--Cover.
Includes index.
Keywords: Web site development; Web sites -- Design; Computer animation; JavaScript (Computer program language).; Computer animation; JavaScript (Computer program language).; Web site development; Web sites -- Design